2013
DOI: 10.3390/md11103582
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles Attenuate Hydrogen Peroxide-Induced Stress Injury in Mouse Macrophage RAW264.7 Cells

Abstract: This study was carried out to investigate the protective effects of chitosan nanoparticles (CNP) against hydrogen peroxide (H2O2)-induced oxidative damage in murine macrophages RAW264.7 cells. After 24 h pre-incubation with CNP (25–200 μg/mL) and chitosan (CS) (50–200 μg/mL, as controls), the viability loss in RAW264.7 cells induced by H2O2 (500 μM) for 12 h was markedly restored in a concentration-dependent manner as measured by MTT assay (P < 0.05) and decreased in cellular LDH release (P < 0.05). Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 39 publications
9
37
0
Order By: Relevance
“…In the present study, animals treated with CCl 4 plus CNPs at the two tested doses showed significant improvements in the hepatic toxicity biomarkers, antioxidant enzymes, oxidative stress markers, tumor markers as well as the significant improvement in the histological picture of the liver. These findings are in harmony with the findings of Wen et al [92] who reported a protective role of CNPs with a mean diameter of 83.66 nm against H 2 O 2 -induced RAW-264.7 cell injury through restoring the activities of endogenous antioxidants (SOD, GPx and CAT), along with enhancement of their gene expression.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, animals treated with CCl 4 plus CNPs at the two tested doses showed significant improvements in the hepatic toxicity biomarkers, antioxidant enzymes, oxidative stress markers, tumor markers as well as the significant improvement in the histological picture of the liver. These findings are in harmony with the findings of Wen et al [92] who reported a protective role of CNPs with a mean diameter of 83.66 nm against H 2 O 2 -induced RAW-264.7 cell injury through restoring the activities of endogenous antioxidants (SOD, GPx and CAT), along with enhancement of their gene expression.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, antioxidant activity of CNs was coupled with their ability to suppress the production of lipid peroxidation, restore activity of endogenous antioxidant and increase total antioxidant capacity. Similar results were shown in in vitro (Wen et al, 2013) and in vivo (El-Denshary et al, 2015) models.…”
Section: Independent Of Oxidative Stress-induced Premature Senescencesupporting
confidence: 76%
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%